1985
DOI: 10.3109/14017438509102824
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Fibronectin Levels After Cardiac and Pulmonary Surgery: Role of Cardiopulmonary Bypass

Abstract: The changes in immunoassayable plasma fibronectin were studied during seven days after cardiac surgery with cardiopulmonary bypass (group A, 19 patients) or lung surgery without bypass (group B, 11 patients). In group A the fibronectin showed a series of rapid changes during the 24 perioperative hours. Simultaneous assessment of other plasma proteins (albumin, fibrinogen and immunoglobulin G) suggested that these changes mainly reflected hemodilution and hemoconcentration processes following the cardiopulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“…8) The fibronectin monitoring did not show any statistically significant decrease in its postoperative levels in any of the groups studied, which was also true for group A prior to adjustment for hemodilution: this finding is not consistent with some past or recent studies that described a postoperative fall to 190 -150 µg/mL. [9][10][11][12] Our finding can be ascribed to an advanced surgical technique and improved extracorporeal circulation (shorter duration, use of the capillary oxygenator instead of the bubble oxygenator, lower priming of the extracorporeal circulation). Based on the fact that no acute fibronectin depletion was detected in any of the groups studied (fibronectin levels over 300 µg/mL are considered slight depletion and those under 250 µg/mL severe depletion), we concluded that the fibronectin dependent physiological mechanisms, namely non-immunoglobulin and complement independent opsonization and reticulo-endothelial potential for phagocytosis, were not altered in the patients studied.…”
Section: Discussioncontrasting
confidence: 45%
“…8) The fibronectin monitoring did not show any statistically significant decrease in its postoperative levels in any of the groups studied, which was also true for group A prior to adjustment for hemodilution: this finding is not consistent with some past or recent studies that described a postoperative fall to 190 -150 µg/mL. [9][10][11][12] Our finding can be ascribed to an advanced surgical technique and improved extracorporeal circulation (shorter duration, use of the capillary oxygenator instead of the bubble oxygenator, lower priming of the extracorporeal circulation). Based on the fact that no acute fibronectin depletion was detected in any of the groups studied (fibronectin levels over 300 µg/mL are considered slight depletion and those under 250 µg/mL severe depletion), we concluded that the fibronectin dependent physiological mechanisms, namely non-immunoglobulin and complement independent opsonization and reticulo-endothelial potential for phagocytosis, were not altered in the patients studied.…”
Section: Discussioncontrasting
confidence: 45%